Harmony Feasibility Trial: Acute and Short-Term Outcomes With a Self-Expanding Transcatheter Pulmonary Valve - Bergersen, Lisa; Benson, Lee N; Gillespie, Matthew J; Cheatham, Sharon L; Crean, Andrew M; Hor, Kan N; Horlick, Eric M; Lung, Te-Hsin; McHenry, Brian T; Osten, Mark D; Powell, Andrew J; Cheatham, John P (JACC. Cardiovascular interventions, 2017)
This study sought to obtain in vivo data to confirm assumptions on device loading conditions and assess procedural feasibility, safety, and valve performance. The Harmony transcatheter pulmonary valve (Medtronic, Minneapolis, Minnesota) was designed for patients with severe pulmonary regurgitation who require pulmonary valve replacement. Three sites participated in this first Food and Drug Administration-approved early feasibility study using an innovative device design to accommodate the complex anatomy of the right ventricular outflow tract. Potentially eligible patients underwent review by a screening committee to determine implant eligibility. Six-month outcomes are reported. Between May 2013 and May 2015, 66 subjects were enrolled, and 21 were approved for implant and underwent catheterization; 20 were implanted. Catheterized patients had a median age of 25 years, were predominantly diagnosed with tetralogy of Fallot (95%), had severe pulmonary regurgitation (95%), and had trivial or mild stenosis. The device was delivered in the desired location in 19 of 20 (95%) patients. Proximal migration occurred in 1 patient during delivery system removal. Two devices were surgically explanted. Premature ventricular contractions related to the procedure were reported in 3 patients; 2 were resolved without treatment. One patient had ventricular arrhythmias that required treatment and later were resolved. At 1 month, echocardiography revealed none or trivial pulmonary regurgitation in all and a mean right ventricular outflow tract gradient of 16 ± 8 mm Hg (range 6 to 31 mm Hg). In this feasibility study of the Harmony transcatheter pulmonary valve device, there was high procedural success and safety, and favorable acute device performance.